Modified recombinant human IgG1‐Fc is superior to natural intravenous immunoglobulin at inhibiting immune‐mediated demyelination. Issue 1 (9th May 2021) - Baksmeier, Christine; Blundell, Pat; Steckel, Julia; Schultz, Verena; Gu, Quan; Da Silva Filipe, Ana; Kohl, Alain; Linnington, Chris; Lu, Dongli; Dell, Anne; Haslam, Stuart; Wang, Jiabin; et al.
Abstract: Intravenous immunoglobulin (IVIG) is an established treatment for numerous autoimmune conditions. Although Fc fragments derived from IVIG have shown efficacy in controlling immune thrombocytopenia in children, the mechanisms of action are unclear and controversial. The aim of this study was to dissect IVIG effector mechanisms using further adapted Fc fragments on demyelination in an ex vivo model of the central nervous system–immune interface. Using organotypic cerebellar slice cultures (OSCs) from transgenic mice, we induced extensive immune‐mediated demyelination and oligodendrocyte loss with an antibody specific for myelin oligodendrocyte glycoprotein (MOG) and complement. Protective effects of adapted Fc fragments were assessed by live imaging of green fluorescent protein expression, immunohistochemistry and confocal microscopy. Cysteine‐ and glycan‐adapted Fc fragments protected OSC from demyelination in a dose‐dependent manner where equimolar concentrations of either IVIG or control Fc were ineffective. The protective effects of the adapted Fc fragments are partly attributed to interference with complement‐mediated oligodendroglia damage. Transcriptome analysis ruled out signatures associated with inflammatory or innate immune responses. Taken together, our findings show that recombinant biomimetics can be made that are at least two hundred‐fold more effective than IVIG in controlling demyelination by anti‐MOG antibodies. Abstract : Adapted Fc fragments protect against antibody‐mediated demyelination in a dose‐dependent manner where equimolar concentrations of either IVIG or control Fc were ineffective. The protective effects of the adapted Fc fragments are partly attributed to interference with complement‐mediated oligodendroglia damage.